The Use of Podcast As an E-Learning Medium in Teaching Vocabulary Students of MI Nurul Huda Serang Cipari Cilacap - Adam Aziz, Vierri (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The spread of Corona Virus diseas (Covid19) impacts vaarious aspects of living system such as social, economic, incredibly educatinal system. The government enacted the chool rom home during the pandemic. Tthere was undoubtedly a change in implementing the teaching and learning process in the Indonesian educational contect. The quick solution is by utilizing podcast as an e-learning medium during the pandemic. MI Nurul Huda Serang, Cilacap is one of th school tthat used podcast as an e-learning medium in the teaching. This research described how podcas used in the learning process at MI Nurul Huda Serang,Cipari, Cilacap. The reearch method used in this research is qualitatiive descriptive method. Data reduction, data display, and vertification data have been used as data analysis teciques of this research. The results showed that the English teacher of MI Nurul Huda used two types of podcast in the teaching vocabulary, namely podcast audio on whatsApp and podcast video on Youtube.